Developing a Model of Islamic Educational Studies based Reading Comprehension Instructional Material through Schema Theory Approach for Tarbiyah Students of IAIN of Bengkulu - Syamsul Rizal (Universitas Negeri Padang, 2014)
Research in developing a model of English instructional materials in accordance with the students’ characteristics of any State Institute for Islamic Studies like STAIN , IAIN and UIN under the Ministry of Religious Affairs of RI in Indonesia has not been done. Therefore, the objective of this research is to develop Islamic educational studies based English instructional material through schema theory approach . The research method was done following Borg and Gall model. Test subjects in the study were all the third semester students of PAI and PGMI department of Tarbiyah Faculty of IAIN Bengkulu in academic year 2013/2014. To evaluate the quality of the instructional material model developed by the researcher were used instrument adiminstered to the expert of teaching material, the expert of media and the English lecturers of IAIN of Bengkulu. Analysis of the data includes: qualitative and quantitative analysis. The results showed: English instructional material of IAIN Bengkulu currently used as a handbook for lecturers and students is not in accordance with the students’ characteristics of Tarbiyah Faculty, the instructional material model developed by the researcher is in appropriate (good) quality, and and positive response from students’ perception.